2013
DOI: 10.1038/nature12295
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion dynamics of hunting in wild cheetahs

Abstract: Although the cheetah is recognised as the fastest land animal, little is known about other aspects of its notable athleticism, particularly when hunting in the wild. Here we describe and use a new tracking collar of our own design, containing a combination of Global Positioning System (GPS) and inertial measurement units, to capture the locomotor dynamics and outcome of 367 predominantly hunting runs of five wild cheetahs in Botswana. A remarkable top speed of 25.9 m s(-1) (58 m.p.h. or 93 km h(-1)) was record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
280
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(288 citation statements)
references
References 29 publications
7
280
1
Order By: Relevance
“…We have shown that for quolls the coefficient of friction is high relative to that of ponies (0.6-0.7), and even cheetahs (1.3) running over compliant grassed surfaces (Tan and Wilson, 2010;Wilson et al, 2013). This may be due in part to the thin rubber matting used on the racetrack in our study, but is also likely to be due to the soft pads and long claws found on the hindfeet and forefeet of northern quolls.…”
Section: Discussionmentioning
confidence: 72%
“…We have shown that for quolls the coefficient of friction is high relative to that of ponies (0.6-0.7), and even cheetahs (1.3) running over compliant grassed surfaces (Tan and Wilson, 2010;Wilson et al, 2013). This may be due in part to the thin rubber matting used on the racetrack in our study, but is also likely to be due to the soft pads and long claws found on the hindfeet and forefeet of northern quolls.…”
Section: Discussionmentioning
confidence: 72%
“…To our knowledge, reliable direct measurements of maximum running speed of ostriches do not exist, despite widespread popular reports of maximum speeds reaching 20-27 m s −1 (45-60 mph). Recent GPS-IMU tracking has allowed direct confirmation of the remarkable top speeds of hunting wild cheetahs (25.9 m s −1 , 59 mph; Wilson et al, 2013). It would be useful to similarly track wild ostriches over extended periods to better relate lab-based measures of locomotor dynamics to those used during foraging, migration and predator escape in the wild.…”
Section: Maximum Running Speeds In Ostrichesmentioning
confidence: 99%
“…However, recent advances in global-positioning systeminertial measurement unit (GPS-IMU) sensing loggers provide a promising new tool for understanding animal locomotor dynamics and behaviour over a broad range of conditions, including long-term field studies and predator-prey interactions (e.g. Wilson et al, 2013;Hubel et al, 2016). The goals of the current study were to (1) develop quantitative methods for measuring detailed bipedal gait dynamics using GPS-IMU sensors and (2) use these methods to measure self-selected gait-speed distributions and walk-run transition speeds in freely moving ostriches in a field-laboratory setting.…”
Section: Introductionmentioning
confidence: 99%
“…The focus is indeed generally on the escape strategies of the prey or on the foraging strategy of the predator, but very seldom of both. Hunting cheetahs are a good example [1]: we now know much about the kinematics and biomechanics of the predator during the chase, but information regarding the prey whereabouts is nearly non-existent, and information about the terrain in which the interaction occurs is systematically absent. The same applies to other predator -prey interactions with very different animals in very different environments: for penguins chasing krill for example [2].…”
Section: Introductionmentioning
confidence: 99%